If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12(x + 2) = 4(3x + 3) + 12 Reorder the terms: 12(2 + x) = 4(3x + 3) + 12 (2 * 12 + x * 12) = 4(3x + 3) + 12 (24 + 12x) = 4(3x + 3) + 12 Reorder the terms: 24 + 12x = 4(3 + 3x) + 12 24 + 12x = (3 * 4 + 3x * 4) + 12 24 + 12x = (12 + 12x) + 12 Reorder the terms: 24 + 12x = 12 + 12 + 12x Combine like terms: 12 + 12 = 24 24 + 12x = 24 + 12x Add '-24' to each side of the equation. 24 + -24 + 12x = 24 + -24 + 12x Combine like terms: 24 + -24 = 0 0 + 12x = 24 + -24 + 12x 12x = 24 + -24 + 12x Combine like terms: 24 + -24 = 0 12x = 0 + 12x 12x = 12x Add '-12x' to each side of the equation. 12x + -12x = 12x + -12x Combine like terms: 12x + -12x = 0 0 = 12x + -12x Combine like terms: 12x + -12x = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 2D+3=13 | | 2x+4+x=4+3x | | 3(-6y+1)+5y=-10 | | B-6b=0 | | y+(13)=61 | | 3(3x-1)+3(3x-1)=5(2x+2) | | s^3+6s^2+11s=0 | | 2896=-40x+83216 | | 8x-2=-9 | | 2896=-40x | | y^2+5y-24=0 | | h=-40x+83216 | | 30+2+(-9)+(-12)= | | 3m^2-9=0 | | -8n-4=-8-7n | | 38=6-8x | | 6t=3(t+4)-1t | | x-3(x+.75)=2x+3 | | 2x^2-5=-7 | | 25x^4-144=y | | 25x^4-144=0 | | 10x+6=-3x+39 | | 9(x+12)-5x=4(x-3) | | -10=1/4(8y-12) | | 7x+4(2-x)=3+5x | | 4(2x-1)=7(x-5) | | 6+6n=n+1 | | -9(10b-10)=0 | | h^2-10h=-32 | | -5(5.25+3.1x)=-6.2(2.5+1.9) | | x+3y+12+5y= | | x+6+x+6=3x-31 |